Development of science and technology parks in China, 1988 - 2008 - Haiyang Zhang; Tetsushi Sonobe (Economics: The Open-Access, Open-Assessment E-Journal, 2011)
In order to investigate the effectiveness of science and technology industrial parks (STIPs), this study examines data on high-tech firms within and outside the STIPs in China, while paying special attention to the issues related to agglomeration and congestion. The main finding is that the negative effect of congestion on productivity is highly likely to outweigh the positive productivity effect of agglomeration economies within the STIPs but not among high-tech firms outside the STIPs. The paper also finds that the productivity of high-tech firms, whether within or outside the STIPs, are positively associated with foreign direct investment and the academic activities of local universities in the same city.
Keywords: O3; O4; 330; Science and technology parks; agglomeration; congestion; China; Technologiezentrum; Agglomerationseffekt; Bottleneck; Hochtechnologiesektor; China